Perbedaan Akibat Hukum Talak Tiga Yang Jatuh Di Luar Dan Didepan Sidang Pengadilan Perspektif Fiqih Empat Mazhab - Rosi Malinda; Fatimatuz Zahro; Moh Nafik (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2023)
Divorce can occur one way or another because of divorce which is the cause of the breakup of the marriage. Talak comes from the word 'ithlaq' which in Arabic means to let go or free. If it is related to marriage, talaq or thalaq means releasing the marriage bond and ending the relationship between husband and wife. Talaq can be referred again as long as the wife is still in the iddah period, namely for the first and second talaq. However, there are several divorce cases, especially talak divorces, in court where the husband has given talaq more than three times, but the Panel of Judges in their decision only gave permission to give talak raj'i to the husband. This gives rise to different legal consequences between divorce outside and in front of the court. This research aims to determine the differences in the consequences of these laws.The type of research in this title is normative juridical research which uses a conceptual approach. In this research, the data collection technique is carried out by collecting primary legal materials and secondary legal materials that are related to the main problem in this research. Then, normative juridical data analysis techniques are presented descriptively by describing the legal consequences of triple talaq outside and in front of the trial. The results of the research show that triple talaq which occurs outside the court session is recognized as valid only in religious terms so that the marriage is terminated when the talaq is imposed, causing the wife to no longer be halal to her husband. Meanwhile, triple talaq before the trial is considered first talaq if the case is the first divorce to be tried, then the legal consequences that arise are that the first talaq law applies. Meanwhile, according to the four Imams of Madzhab, talaq is determined by what the husband intends. There is no obligation to impose talaq in front of the court because the talaq belongs entirely to the husband. The purpose of talaq in front of the court is to protect the rights of the wife and children after divorce.